Revisiting Predictions about the Future of Human Life in 20th Century American Sci-Fis - Jatmiko, Rahmawan (Rubikon : Journal of Transnational American Studies, 2024)
Predictions and illustrations of life in the future are often integrated in works of science fiction, which could not be immediately proven yet possibly fascinating when looked back on several decades later or at the times predicted in the works. Science fiction authors foretell such events by borrowing theories, concepts, or simply terms used by scientists. Those theories, concepts, and terms can be written in scientific journals or in more popular media. American science fiction works, for instance, illustrate the future by their adaptation in the forms of more popular media such as movies, video games, and the works categorized as the subgenres of cyber literature. All of them are discussed in this paper from the lens of New Historicism, which believes in equality between literary and non-literary texts in viewing phenomena that exist in society, one of which is the relationship between science fiction works, their writers, their readers, and society. Technology is seen as a product of society, so it becomes broadly part of culture. Meanwhile, emerging technology is sometimes coincidental and random, so it can also be seen that technology determines people’s movements and lifestyles. This study contributes to ongoing discussions on the ethical and societal implications of speculative narratives by highlighting the interconnectedness between literature, science, technology, and society.